2020
DOI: 10.1111/dth.13941
|View full text |Cite
|
Sign up to set email alerts
|

A randomized split‐face, investigator‐blinded study of a picosecond Alexandrite laser for post‐inflammatory erythema and acne scars

Abstract: The 755 nm picosecond Alexandrite laser has been demonstrated to be effective and well tolerated in patients with acne scars. In this split-face, investigator-blinded study, 16 patients with post-inflammatory erythema (PIE) and acne scars were randomized to receive laser treatment on half the face, with the other half serving as a control. The treatment side demonstrated a significant improvement in both PIE and scars compared to the baseline and also when compared to the control side. Treatment was well-toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 9 publications
0
38
0
Order By: Relevance
“…However, repetitive sessions were required to obtain an effective response. Pro‐yellow laser has achieved effective results even in a one single session, especially in postacne erythema 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, repetitive sessions were required to obtain an effective response. Pro‐yellow laser has achieved effective results even in a one single session, especially in postacne erythema 1 …”
Section: Discussionmentioning
confidence: 99%
“…Acne vulgaris is one of the most common dermatological disorders seen in adolescents. Postacne scars and erythema may be seen in up to 80% of patients with severe acne an even may be permanent in fair‐skinned population 1 …”
Section: Introductionmentioning
confidence: 99%
“…No new adverse reactions were found, showing that the 1,064/532 nm picosecond laser therapy has satisfactory safety. Conversely, Wen et al (26) in the recent study showed some efficacy of picosecond Alexandrite laser in treating post-inflammatory erythema, implying that the LIOB effect may be used in erythema reduction and in stimulating collagen production.…”
mentioning
confidence: 95%
“…Picosecond lasers deliver pulse durations in the picosecond range, much shorter, depending on the specifications of the individual device, than traditional nanosecond Q-switched lasers. 47 Additionally, picosecond lasers deliver lower fluences allowing these devices to generate a greater photoacoustic effect with less photothermal damage. 47 Wen et al demonstrated a statistically significant reduction in erythema using the Clinician Erythema Assessment Scale (CEAS) as well as a significant improvement in acne scars with minimal side effects in a split-face randomized study investigating the use of a 755nm picosecond Alexandrite laser for the treatment of post-inflammatory erythema and acne scarring.…”
Section: Lasersmentioning
confidence: 99%
“… 47 Additionally, picosecond lasers deliver lower fluences allowing these devices to generate a greater photoacoustic effect with less photothermal damage. 47 Wen et al demonstrated a statistically significant reduction in erythema using the Clinician Erythema Assessment Scale (CEAS) as well as a significant improvement in acne scars with minimal side effects in a split-face randomized study investigating the use of a 755nm picosecond Alexandrite laser for the treatment of post-inflammatory erythema and acne scarring. 47 Further studies investigating the role of picosecond lasers in the management of facial erythema are needed before reaching a conclusion regarding its utility in management of this common condition.…”
Section: Lasersmentioning
confidence: 99%